Delineating a locus conferring Fusarium crown rot resistance on chromosome arm 1HL in barley by developing and analysing a large population derived from near isogenic lines - Shang Gao; Zhi Zheng; Haiyan Hu; Yunfeng Jiang; Miao Liu; Jiri Stiller; Meixue Zhou; Chunji Liu (Crop Journal, 2020)
Fusarium crown rot (FCR), a chronic and severe disease caused by various Fusarium species, is prevalent in semi-arid cropping regions worldwide. One of the major QTL conferring FCR resistance was detected on chromosome arm 1HL (Qcrs.cpi-1H) in barley. To develop markers that can be reliably used to incorporate the resistance locus into breeding programs, we developed and assessed a near-isogenic line-derived population consisting of 1180 recombinant inbred lines targeting the locus. Using this population, we delineated Qcrs.cpi-1H into an interval of 0.4 cM covering a physical length of about 487 kb. Six markers co-segregating with this locus were generated. Co-linearity for genes located in this interval between the genome of barley and those of either rice or Brachypodium distachyon is poor. Three genes with non-synonymous variations between the resistant and susceptible lines were identified within the interval. The results reported in this study not only provide markers for integrating Qcrs.cpi-1H into breeding programs, but also form a solid foundation for cloning the causal gene(s) underlying this locus.